2015
DOI: 10.1007/s10836-015-5523-7
|View full text |Cite
|
Sign up to set email alerts
|

A Hilbert-Transform-Based Method to Estimate and Correct Timing Error in Time-Interleaved ADCs

Abstract: In time-interleaved analog-to-digital converter (ADC) architecture, offset mismatch, gain mismatch, and timing error between channels degrade the performance of time-interleaved ADCs. This paper focuses on the timing error, and proposes a simple calibration algorithm based on Hilbert transform estimate and then correct the timing error. With a cosine input, it could efficiently and accurately estimate the timing error. Fractional delay filters are developed to correct the timing errors. This simplifies the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The interpretation of (20) depicts that the first term on the right side of equality is the representation of timing skew mismatch. The second term illustrates the gain error just as obtained in (14), while the fourth phrase pertains to the offset mismatch. The third term, which is the product of timing skew and gain mismatches, is small enough to be neglected.…”
Section: The Effect Of Triple Errors All Togethermentioning
confidence: 99%
See 3 more Smart Citations
“…The interpretation of (20) depicts that the first term on the right side of equality is the representation of timing skew mismatch. The second term illustrates the gain error just as obtained in (14), while the fourth phrase pertains to the offset mismatch. The third term, which is the product of timing skew and gain mismatches, is small enough to be neglected.…”
Section: The Effect Of Triple Errors All Togethermentioning
confidence: 99%
“…A comprehensive literature review depicts that many state-of-the-art architectures have been reported over recent years for the foreground calibration of TI-ADCs. [13][14][15][16][17][18] Even though the main objective was to reduce the utilized hardware, few of them slightly managed to achieve such a goal because specific signal reconstruction procedures are needed as a substitution for the reference ADC. For a better realization of the issue, the specifications of those systems have been summarized in Table 1.…”
Section: Hardware Complexity Of the Calibration Schemesmentioning
confidence: 99%
See 2 more Smart Citations
“…The calibration uncertainty of this system reaches 0.038% within the measuring range. The hardware compensation method circuit [8,9] is usually complicated, and the circuit design process costs much. Besides, the calibration range is small, and the accuracy cannot be guaranteed within the entire range.…”
Section: Introductionmentioning
confidence: 99%